(untitled) (Medical Forum Monthly, 2024)
Objective: Types of operative measures adopted and prognosis of patients with perforating injuries to colon. Study Design: Descriptive Study Place and Duration of Study: This study was carried out in the Surgical Unit-I, Nishtar Medical College, Multan during the period from July 2011 to December 2011. Material and methods: All 60 patients were admitted in emergency ward with trauma to abdomen, and routine investigations were carried out. Results: Majority of the patients i.e. 51 (85%) were injured by gunshot. Fifty five (90%) patients were male. For more extensive contamination colostomy gave complication rate 20% in grade 2 and 25% in grade-3. Patients who were anastomosed, 15% developed leakage. Out of 60 patients, 15 (25%) patients had injury at right colon, 16 (28%) had at transverse colon, 28 (46%) patients at left colon and remaining 11 (18%) patients had injury at sigmoid colon. Out of 60 patients, 10 (16%) patients were found in injury grade–1, 44 (74%) patients in grade-2 and 6 (10%) patients in injury grade-3 were involved. Majority of the patients i.e. 44 (74%) had more complications. There was no difference between these two groups with respect to grade of colon injury according to the colon injury severity scale or location of injury. Conclusion:- It was observed from data that selective primary repair may be used in a significant proportion of colon wounds. It was based on classification system that employs an assessment of the extent of tissue injury, degree of fecal contamination, assessment of associated injuries; estimates of the influences of delay between injury and definitive therapy and hemorrhagic shock.